ANALISIS PELESTARIAN BAHAN PUSTAKA TERCETAK DI PERPUSTAKAAN KOLESE SANTO IGNATIUS YOGYAKARTA - Suci Yanti Ramadhan (Jurnal Pustaka Ilmiah, 2019)
This study aims to determine the preservation of literature in the St. Ignatius College Library. The method of data collection is through interviews and observation. This type of research is descriptive qualitative. The results showed that in applying the collection preservation process, there were a number of things that were done by the St. Ignatius College Library, namely; 1) Preservation: Use of catalog cards and control cards; closed service; and allocation of funds of 10 to 20 percent; 2) Conservation: setting room temperature (26 degrees Celsius); room humidity up to 62 Hg; carry out fumigation and administration of borax regularly; and clean the book with a special small broom; 3) Restoration: Repair of damaged books is carried out by circulation officers so that repairs to one book can take a long time.